Dimensions of fear in rural Sebuano adolescents - Elwood, Bettie Carroll 1930- (1979)
This study introduced a contextual theory to account for the dimensionality or comprehensiveness of fear among the Sebuano adolescents. Two hundred forty (240) adolescents0 from three public secondary schools in Negros Oriental were asked to appraise their environment regarding its threatening stimuli. A research instrument was designed with three distinctive features: 1) the combination of self study with basic research, 2) a provision for the immediate and local utilization of research findings, and 3) an allowance for later cross-cultural and intra-cultural research. The survey results showed that fears in the metaphysical dimension dominate all other fears while fears in the ecological dimension cause the least trouble for students.
Mimeographed.
Thesis (Ph.D.)--University of the Philippines Diliman.
Vita.
Keywords: Fear; Adolescent psychology -- Philippines -- Cebu